2017
DOI: 10.1093/cvr/cvx178
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of vascular smooth muscle cell calcification by syndecan-4/FGF-2/PKCα signalling and cross-talk with TGFβ

Abstract: AimsVascular calcification is a major cause of morbidity and mortality. Fibroblast growth factor-2 (FGF-2) plays an instructive role in osteogenesis and bone development, but its role in vascular calcification was unknown. Therefore, we investigated the involvement of FGF-2 in vascular calcification and determined the mechanism by which it regulates this process.Methods and resultsWe demonstrate that FGF-2 expression is increased in vascular smooth muscle cells (VSMCs) induced to deposit a mineralized matrix b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 42 publications
2
28
1
Order By: Relevance
“…We show that TGF-β1-induced SMAD2 phosphorylation is increased in PKCα siRNA-treated VSMCs and that extensive phosphorylated SMAD2 expression is detected in calcified aortic arches from PKCα -/mice. As we have previously shown that inhibiting TGF-β receptor signaling with SB431542 prevents the increase in mineralization observed in PKCα siRNA-treated VSMCs in vitro 20 , these data suggest that loss of PKCα increases calcification both in vitro 20,33 and in vivo by upregulating TGF-β/SMAD2 signaling in VSMCs.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…We show that TGF-β1-induced SMAD2 phosphorylation is increased in PKCα siRNA-treated VSMCs and that extensive phosphorylated SMAD2 expression is detected in calcified aortic arches from PKCα -/mice. As we have previously shown that inhibiting TGF-β receptor signaling with SB431542 prevents the increase in mineralization observed in PKCα siRNA-treated VSMCs in vitro 20 , these data suggest that loss of PKCα increases calcification both in vitro 20,33 and in vivo by upregulating TGF-β/SMAD2 signaling in VSMCs.…”
Section: Discussionsupporting
confidence: 73%
“…Six-micron sections were cut using a Microm HM 355S and dried overnight at 37°C. Tissue sections, every 60 microns, were analyzed for calcification by staining with von Kossa and counterstaining with nuclear fast red 20 . Images were acquired on a 3D-Histech Pannoramic-250 microscope slide-scanner using a 40x/0.95 Plan Apochromat objective (Zeiss).…”
Section: Histologymentioning
confidence: 99%
See 2 more Smart Citations
“…We observed specific calcified structures in the M‐side of clubfoot for the first time (Figure ). This could bring a direct connection with overexpression of asporin (which plays a role in biomineralization), TGFβip (essential for TGFβ signaling), and the intracellular pool of TGFβ (relationships to collagen calcification) in the M‐side. Moreover Seki et al declared that overexpressed CILP suppressed TFGβ signaling in lumbal disc disease .…”
Section: Discussionmentioning
confidence: 99%